USING OF CIRCUMSTANCES IN JOE BIDEN’S INAUGURATION SPEECH FROM ENGLISH TO INDONESIAN TRANSLATION - Muh Kholiq (Elite : English and Literature Journal, 2021)
This research aimed to identify the types of circumstances used in Joe Biden’s inauguration speech. This research used the transcript in English version and Indonesian version of Joe Biden’s inauguration speech on January 21, 2021 in Washington DC as the source of the data. Furthermore, the researcher applied a qualitative descriptive method of this research. This result of research showed that there are 37 data found in the type of circumstances such as (2) extent, (2) location, manner divided into (3) means, (7) quality, (3) comparison, (3) degree, cause divided into (4) reason, (4) purpose, and (2) behalf. Moreover, accompaniment consists of (1) comitative. Role has (4) guise category, (1) matter, and angle has (1) in viewpoint category. Moreover, the dominant circumstances that present are quality categories in circumstances of manner.